Individual and combined effects of berberine and santonin on spore germination of some fungi - Singh B.; Srivastava J.S.; Khosa R.L.; Singh U.P. (My University, 2025)
Berberine and santonin were isolated from rhizomes of Berberis aristata and unexpanded flower buds of Artemisia maritima, respectively. Efficacy of these two chemicals individually as well as of their mixtures, was tested against spore germination of some saprophytic and obligate fungi. While berberine individually was effective against most of the fungi, Helminthosporium spp. were least affected even at the highest dose (1500 ppm). Santonin was equally effective against several fungi. Mixture of both alkaloids found to be more effective than individual ones. Keeping the dose of berberine constant and santonin at two different concentrations (viz. 250 and 500 ppm) the spore germination of Helminthosporium oryzae was stimulated. Increasing concentration of santonin inhibited the spore germination of all other fungi tested, Colletotrichum capsici being affected only by 20 and 5 % (at berberine concentration of 250 and 500 ppm, respectively). On the other hand, santonin being constant and berberine at different concentrations, the mixture was effective against all the fungi.